2006
DOI: 10.1002/rcm.2823
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric evidence for different complexes of peptides and proteins with arsenic(III), arsenic(V), copper(II), and zinc(II) species

Abstract: Trivalent and pentavalent arsenic were incubated with sulfur-containing amino acid, peptide and protein solutions both as organic compounds (phenylarsine oxide, phenylarsonic acid, dimethylarsinic acid, monomethylarsonic acid) and as inorganic compounds (arsenite, As(III), and arsenate, As(V)). After incubation of phenylarsine oxide solutions with cysteine and glutathione the mass spectra showed a covalent bond between arsenic and sulfur, which was stable at both acidic and neutral pH values. The mass spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 32 publications
(26 reference statements)
5
51
0
Order By: Relevance
“…The oxidation potential of Zn(II) (E Zn(0)/Zn(II) h = -0.7628 V) is not sufficient to oxidize GSH (E GSH/GSSG h = -0.240 V). This finding agrees with mass spectrometric Cu and Zn binding studies of GSH [9]. The standard redox potential of the Ni(0)/Ni(II) redox pair (E Ni(0)/Ni(II) h = -0.236 V) resembles the potential of GSH/GSSG.…”
Section: Capillary Electrophoretic Evaluation Of Heavy Metal Interactsupporting
confidence: 84%
See 2 more Smart Citations
“…The oxidation potential of Zn(II) (E Zn(0)/Zn(II) h = -0.7628 V) is not sufficient to oxidize GSH (E GSH/GSSG h = -0.240 V). This finding agrees with mass spectrometric Cu and Zn binding studies of GSH [9]. The standard redox potential of the Ni(0)/Ni(II) redox pair (E Ni(0)/Ni(II) h = -0.236 V) resembles the potential of GSH/GSSG.…”
Section: Capillary Electrophoretic Evaluation Of Heavy Metal Interactsupporting
confidence: 84%
“…Further, GSH serves as precursor for the biosynthesis of metal-chelating polypeptides involved in metal detoxification and homeostasis [8]. Instead of a direct binding, metal ions characterized by a large oxidation potential, such as Cu(II) oxidize GSH to GSSG [9]. A large number of studies demonstrated that the GSH/GSSG ratio can be considered as a reliable index of the cellular redox state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gluthione, PCs and its derivatives are considered to be the most important classes of metal-chelating polypeptides, which contain thiol groups that bind readily with arsenic species (Hall 2002;Schmöger et al 2000;Schmidt et al 2007). These peptides can be found in many higher plants like Holcus lanatus, Cytisus striatus and Pteris vittata Hartley-Whitaker et al 2002;Schmöger et al 2000;Zhao et al 2003) and fungi (Kneer and Zenk 1992) and may be partitioned inside vacuoles to facilitate appropriate control of the cytoplasmic concentration of heavy metal ions (Cobbett and Goldsbrough 2002).…”
Section: Complexation With Gsh and Pcsmentioning
confidence: 99%
“…The most important classes of metal-chelating polypeptides are glutathione (GSH) and its derivative forms, phytochelatins (PCs) which contain thiol groups that bind readily with As species (Schmidt et al 2007). These peptides can be found in microalgae, related eukaryotic photosynthetic organisms, and some fungi (Perales-Velaet et al 2006) as organometallic complexes.…”
Section: Introductionmentioning
confidence: 99%